Britishness, belonging and citizenship - Prabhat, Devyani (Policy Press, 2018)
Available Open Access under CC-BY-NC licence. Long term resident migrants to the UK, who often possess valuable skills for the economy, still face significant barriers to citizenship. In this important book, Dr Prabhat captures the experiences of those who successfully become British citizens through stories of belonging, citizenship and the law; beautifully illustrated by artist Sam Church. Speaking to contemporary times of Brexit, the book exposes the challenges which become insurmountable for many migrants, and illuminates the gap between policy and practice in gaining British citizenship.